Pengembangan E-Modul Berbasis Penelitian untuk Meningkatkan Keterampilan Laboratorium dalam Perkembangan Hewan bagi Mahasiswa Pendidikan Biologi - Sutrisnawati Mardin; Achmad Ramadhan; Dwi Setyorini (Jurnal Penelitian Pendidikan IPA, 2025)
The integration of digital learning resources in higher education necessitates innovative instructional materials to enhance students' laboratory competencies. This study aims to develop a research-based e-module for the Animal Development course and evaluate its validity, feasibility, and effectiveness. The research employed the 4D development model—Define, Design, Develop, and Disseminate, focusing on expert validation and small-group trials. Validation results indicate a high validity score (93.28), while student feasibility assessments show strong acceptance (84.2%). An N-Gain test involving 27 students demonstrates a substantial improvement in laboratory skills (N-Gain = 0.79). These findings confirm that the research-based e-module enhances conceptual understanding, improves laboratory practices, and strengthens students’ data analysis abilities. Overall, the developed e-module serves as an effective digital resource for improving laboratory-based learning in Biology Education